Optimization and Mechanical Characteristics of AA6061/Zirconia Nanocomposites Fabricated by Ultrasonic-Aided Stir Casting Method. (20th September 2022) - Gacem, Amel; Refat, Moamen S.; Ali, H. Elhosiny; Naidu, S. C. V. Ramana Murty; Beenarani, B.; Deole, Pranjali; Kumar, S. Sandeep; Rama, S.; Alsuhaibani, Amnah Mohammed; Diriba, Abdi
Abstract : Using the Taguchi Grey response surface approach, this study investigates the effect of novel ultrasonic-aided stir casting conditions on the production of AA6061/zirconia nanocomposites. A Taguchi L16 orthogonal array was utilized to conduct the researches, which included ultrasonic power (1.75-2.5 kW), time (5-20 min), temperature (750-900°C), which can cause premature solidification, stir pressure (100-250 MPa), and reinforcement weight percentage (wt% of reinforcement). Ultrasonic-aided stir casting technique has five adjustable parameters (2-5). The ultimate tensile strength, elongation percentage, hardness, and size of the grain material were some of the metrics used to evaluate the process performance. It was decided to employ the response surface approach to model and optimize the numerous replies into one grey relational analysis. AA6061/zirconia nanocomposites were studied using statistical methods such as 3D surface plots and variance analysis. 2.2537 kW, 16.28 min ultrasonic duration, weight % of reinforcement of 1.9, stirring temperature of 700.73°C, and stirring pressure of 142.63 MPa were found to be the best parameter values.